2021
DOI: 10.1177/1535759721994807
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Diagnostic Gap in Epilepsy: Recognizing More Than Just Motor Seizures

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These surveys have effectively demonstrated that epilepsy stigma persists universally across different regions, regardless of resources, levels of education, and socioeconomic status. [15] Regrettably, executing door-to-door surveys proves arduous in numerous areas where epilepsy is burdened by substantial social stigma. Individuals grappling with epilepsy may exhibit hesitancy in divulging their medical background, particularly if they endure intermittent seizures or witness a deterioration in their condition.…”
Section: Disease Knowledge Gapsmentioning
confidence: 99%
“…These surveys have effectively demonstrated that epilepsy stigma persists universally across different regions, regardless of resources, levels of education, and socioeconomic status. [15] Regrettably, executing door-to-door surveys proves arduous in numerous areas where epilepsy is burdened by substantial social stigma. Individuals grappling with epilepsy may exhibit hesitancy in divulging their medical background, particularly if they endure intermittent seizures or witness a deterioration in their condition.…”
Section: Disease Knowledge Gapsmentioning
confidence: 99%
“…Within neurology, this has been particularly successful for stroke treatment, in which public awareness campaigns, mnemonics, and quality improvement have dramatically improved the quality of care ( 9 ). In designing public awareness campaigns, it is important to understand baseline public knowledge on the topic through utilization of qualitative methods so that such efforts can be aimed at improving true gaps in awareness and knowledge ( 10 , 11 ). To date, this represents a relative shortcoming in the literature, as baseline public knowledge has been largely investigated through survey studies in different regions around the world rather than using qualitative methods.…”
Section: Seizure Recognitionmentioning
confidence: 99%